Avaliação da imunoexpressão de LGR5 e LGR6 em células-tronco no câncer gástrico primário, metástases linfonodais e mucosa gástrica histologicamente normal - Valiente, Adriana Estela Flores (2017)
Gastric cancer is the fourth most common neoplasm in the world and the second leading cause of cancer mortality. Despite the treatment with surgery and chemotherapy, the overall five-year survival of patients with gastric cancer remains low, a possible explanation for less effective therapy is the presence of cancer stem cells. Several markers, including LGR5 and LGR6, have been reported as markers of normal and cancerous stem cells. LGR5 and LGR6 are transmembrane proteins of the G protein group, rich in leucine residues, that participate in cell signaling pathways and activate transcription factors related to tumor formation. The objective of this work was to evaluate the immunoexpression of LGR5 and LGR6 as possible markers of stem cells in primary gastric cancer, lymph node metastases and histologically normal gastric mucosa through tissue microarray and immunohistochemistry techniques. The cross-sectional and observational study was carried out from eighty-eight (88) pieces of gastrectomies due to gastric carcinomas performed at the Walter Cantídio University Hospital, which are part of the Archives of the Service of Pathology and Legal Medicine of the Federal University Of Ceará. The relationships between LGR5 and LGR6 differential expression and clinical-pathological characteristics were assessed by the chi-square test or Fisher's exact test. A value of p <0.05 was considered statistically significant. Positive (from previous reports) were considered cases that presented one or more cells with cytoplasmic or membrane immunostaining. LGR5 was shown to be a potential biomarker, more characteristic of tumor and non-tumor stem cells, than LGR6 in this study. Both are expressed in tumoral and non-tumoral tissue, predominantly in histologically normal mucosa, in a basal third of epithelial thickness. Positive LGR5 predominated in the diffuse histotype and LGR6 in the intestinal type of gastric carcinomas. In the positive cases of the two biomarkers, marked cells are infrequent or rare, in the total cells of the tumor mass and the normal gastric mucosa.